2023
DOI: 10.1037/tra0001322
|View full text |Cite
|
Sign up to set email alerts
|

Unpacking the effects of child maltreatment subtypes on emotional competence in emerging adults.

Abstract: Objective: Child maltreatment is often studied as a general category or individually as a subtype, but maltreatment subtypes are rarely studied simultaneously. Despite a breadth of research in the effects of child maltreatment on emotional competence, discrepant findings emerge when child maltreatment subtypes are explored. The present study aims to better understand the differential effects of childhood maltreatment subtypes on facets of emotion regulation and the recognition of specific emotions. Method: A s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 61 publications
1
4
0
Order By: Relevance
“…In that light, our study elaborates on previous research that found distinct effects of subtypes of abuse on emotion regulation difficulties in adulthood 49,50 . The current findings show that emotional neglect predominates in the prediction of both trait anger and borderline personality traits, whereas physical abuse predominates in the prediction of anger attacks and antisocial personality traits.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In that light, our study elaborates on previous research that found distinct effects of subtypes of abuse on emotion regulation difficulties in adulthood 49,50 . The current findings show that emotional neglect predominates in the prediction of both trait anger and borderline personality traits, whereas physical abuse predominates in the prediction of anger attacks and antisocial personality traits.…”
Section: Discussionsupporting
confidence: 81%
“…48 In that light, our study elaborates on previous research that found distinct effects of subtypes of abuse on emotion regulation difficulties in adulthood. 49,50 The current findings show that emotional neglect predominates in the prediction of both trait anger and borderline personality traits, whereas physical abuse predominates in the prediction of anger attacks and antisocial F I G U R E 3 Heat plot of correlations between childhood trauma (i.e., CTI, Childhood trauma index; CTQ-SF), childhood life events, anger measures (i.e., Trait anger, Anger attacks, PDQ-4 Borderline, PDQ-4 Antisocial), and symptom severity measures (i.e., IDS-SR, BAI, FQ, PSWQ). We used a sum score for the dichotomous variables anger attacks, PDQ-4 Borderline, and PDQ-4 Antisocial using the 5, 9, and 7 items respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Higher PTG scores mean that many participants expressed having undergone transformative changes when recovering from the devastation brought on by their traumatic experience (Jankovic et al, 2022 ; Tedeschi & Calhoun, 2004 ). Additionally, emotional maltreatment, and physical abuse to a lower extent (Cheng & Langevin, 2022 ; Kim et al, 2023 ), have been identified as the most damaging subtypes of CM for emotion regulation, and upon close examination, the BRS items could be construed as indicators of emotion regulation abilities in high stress situations (e.g. ‘It does not take me long to recover from a stressful event’).…”
Section: Discussionmentioning
confidence: 99%
“…The most common dimension for operationalizing child maltreatment is through the categorization of distinct types (e.g., physical abuse, sexual abuse, emotional neglect) (Jackson et al, 2019). Studies suggest that individual types of maltreatment may contribute specifically or in a shared manner to later outcomes (Cecil et al, 2017;Cheng & Langevin, 2022). For example, a study of emerging adults found that a history of emotional abuse contributed globally to the dimensions of emotional regulation, whereas other types of maltreatment (e.g., neglect) contributed individually to specific facets of emotional regulation (e.g., impulsivity) (Cheng & Langevin, 2022).…”
Section: Importance Of Research On Specific Characteristics Of Child ...mentioning
confidence: 99%
“…Studies suggest that individual types of maltreatment may contribute specifically or in a shared manner to later outcomes (Cecil et al, 2017;Cheng & Langevin, 2022). For example, a study of emerging adults found that a history of emotional abuse contributed globally to the dimensions of emotional regulation, whereas other types of maltreatment (e.g., neglect) contributed individually to specific facets of emotional regulation (e.g., impulsivity) (Cheng & Langevin, 2022). Additionally, most research on child maltreatment and later outcomes has focused on physical and sexual abuse (Angelakis et al, 2019;Baldwin et al, 2019;Norman et al, 2012).…”
Section: Importance Of Research On Specific Characteristics Of Child ...mentioning
confidence: 99%